A green technique to prepare uniform amine capped multi-walled carbon nanotubes to fabricate high strength, protein resistant polymer nanocomposites. Issue 20 (6th March 2015) - Das, Tanya; Roy, Sunanda; Ting, Sun; Zhang, Liying; Li, Yongmei; Yue, Chee Yoon; Hu, Xiao
<x xml:space="preserve">Abstract</x> Efficient amine grafting on MWCNTs by double UV-ozone induced grafting, and its role in biomaterials.